2014
DOI: 10.1519/jsc.0000000000000288
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Motivational Variables in CrossFit Facilities

Abstract: CrossFit is a growing fitness trend in the United States; however, little systematic research has addressed specific motivational principles within this unique exercise environment. The purpose of the study was to explore the influence of gender and membership time on perceptions of motivational climate and goals within the CrossFit environment. Specifically, people may set goals related to self-improvement (i.e., mastery) or focus on their performance in comparison to others (i.e., performance). Motivational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 27 publications
3
40
0
4
Order By: Relevance
“…As noted before, this research is not attempting to determine gender equity but rather explore the ways in which gender is given meaning through the images used in the journal. Previous research conducted by Partridge, Knapp, and Massengale (2014) found that the coed nature of participation in CrossFit may have a positive affect in terms of decreasing perceived gender differences which is another reason for including the coed photographs in this current research study. The analysis will be concerned with not only the amount of coverage but also the messages about sex differences that are encoded within the images.…”
Section: Discussionmentioning
confidence: 90%
“…As noted before, this research is not attempting to determine gender equity but rather explore the ways in which gender is given meaning through the images used in the journal. Previous research conducted by Partridge, Knapp, and Massengale (2014) found that the coed nature of participation in CrossFit may have a positive affect in terms of decreasing perceived gender differences which is another reason for including the coed photographs in this current research study. The analysis will be concerned with not only the amount of coverage but also the messages about sex differences that are encoded within the images.…”
Section: Discussionmentioning
confidence: 90%
“…Traditional gym-based exercise is the primary method used to increase exercise levels through exercise referral schemes in the UK. The present study examines a novel gym environment, CrossFit, which is fast growing in popularity (Partridge et al, 2014). CrossFit began as a training regime originally founded by Greg Glassman in California, United States of America in the mid-nineties.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, there was moderate between participant variation in the maximum strength of the participants; however, there was a large range in the self-reported 1RM's (85 -150 kg) and this led to the time to complete the protocol ranging extensively from 62 seconds (strongest athlete) to 520 seconds (weakest athlete). In many extreme conditioning programs that combine technical resistance exercises and highly fatiguing routines there is the potential to scale the program to an athlete's ability by manipulating the exercise, load or other relevant factors [18]. However, in many cases there will exist a large range in strength between athletes using the same resistance and the results from this study highlight a potential difficulty in training prescription of a system that frequently uses absolute loads.…”
Section: Discussionmentioning
confidence: 94%